A Guerra ao Terror e o cinema estadunidense pós-11 de setembro de 2001 - Matos, Daniel Ivori de (2018)
This thesis takes as its theme one of the highest profile events in this short twenty-first century, the terrorist attacks of September 11, 2001 in the US. Initially, there is the exploitation of the event images as a new milestone that shook the nation; then terrorism took over the agenda, many political speeches by then-President George Walker Bush on the new enemy, terrorism, were appropriated by several rulers, becoming an international counter-terrorism strategy, which justified legislative changes in the US, boosted the conflicts in Afghanistan and Iraq, incorporating further discussions on the Middle East and Islam. Understand that this chapter of US history is impossible to write without the images, since the spectacularization of the images of the attacks had a great impact on American society. The films in this process is established as a significant practical, for or against such subject, thus, we sought to understand through the film, and September 11 were affected filmic understood and written Hollywood, that is, how this milestone was incorporated and expressed in innumerable ways through the strategies of the language / aesthetics of the cinematographic narrative and how they were received by the American critics. Highlighting the production Syriana (2005), understood as the dissonant note amid the filmography of the period. Thus, an analysis of the film records referring to the War on Terror undertaken by the USA and its reception is realized, perceiving the cinema as an artistic expression and historical agent.